Effect of Defects Parameters of Welded Joints on Fatigue Life using Finite Element Analysis - Abdullatif, Laila F.; Saleh, Nathera A. (Basrah Journal for Engineering Sciences, 2022)
The present investigation’s main goal is to assess butt joint and T-joint plates containing misalignment, undercut and porosity welding defects by studying the influence of the defect’s parameters on the fatigue life. The fatigue life is predicted using ANSYS ver. 19 Software. The results of finite element analysis are used in the regression analysis to find relationship between the fatigue life and defects parameters. The findings demonstrated that finite element modeling and the pervious published experimental tests were in good agreement with maximum error percentage 4 %. The fatigue life differed substantially depending on the defect’s parameters.